Printable superhydrophilic-superhydrophobic micropatterns based on supported lipid layers - Li, Junsheng; Li, Linxian; Levkin, Pavel (Langmuir, 2012)
A new and simple method for creating superhydrophilic micropatterns on a superhydrophobic surface is demonstrated. The method is based on printing an “ink”, an ethanol solution of a phospholipid, onto a porous superhydrophobic surface and, thus, is compatible with a variety of commonly available printing techniques.